Motivasi Belajar dan Perhatian Orang Tua: Apakah Mempengaruhi Hasil Belajar pada Masa Pandemi Covid-19? - Iyakrus Iyakrus; Ibrahim Mikail; Meirizal Usra; Waluyo Waluyo; Wahyu Indra Bayu (Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2022)
The purpose of this study was to findout whether there was a relationship between the motivation and attention of parents with the learning outcomes of PJOK subjects during the Covid-19 pandemic at SMP Negeri 38 Palembang. The research method used in this research is quantitative research methods with correlation analysis. With a sample of 60 students of class VII (Male 31, Female 29), and data collection using a questionnaire. The results showed that learning motivation and parental attention affected learning outcomes (rxy: 0.82, p<0.05; rxy: 0.708, p<0.05). The conclusion of this research is that there is a significant relationship between learning motivation and parental attention with the learning outcomes of PJOK subjects during the Covid-19 pandemic at SMP Negeri 38 Palembang.